Effect of dopamine infusion on gastric and pancreatic secretion and on gastrin release in man. Issue 8 (August 1978) - Caldara, R; Ferrari, C; Romussi, M; Bierti, L; Gandini, S; Curtarelli, G
Abstract : The effect of dopamine infusion on basal and pentagastrin-stimulated gastric secretion, on basal and secretin-CCK-PZ-stimulated pancreatic secretion, and on basal and meal-induced gastrin release has been evaluated in healthy volunteers. Both basal and stimulated gastric acid secretion were significantly inhibited during dopamine infusion with a significant rebound to pre-infusion values after discontinuing dopamine. These effects were prevented by pretreatment with the antidopaminergic drug, metoclopramide. A slight but now significant decrease in amylase and bicarbonate outputs was also observed during dopamine infusion, while gastrin release did not change. These data suggest the existence of dopaminergic mechanisms in the regulation of gastric acid secretion in man.